Who am I? : an autobiography of emotion, mind, and spirit - Tuan, Yi-fu, 1930-2022 (Madison : University of Wisconsin Press, 1999)
"Who Am I? is the bittersweet memoir of a Chinese American who came to this country as a twenty-year-old graduate student and stayed to become one of America's most innovative intellectuals, whose work has explored the aesthetic and moral dimensions of human relations with landscape, nature, and environment."--Jacket
"Yet, Tuan finds his life increasingly marked by detachment and isolation. In Who Am I?, he probes what he sees as his moral failings, his lack of courage - including the courage to be open about his homosexuality - resulting, as he writes, "in a life that is seamed in ambivalence - achingly empty at the core, despairingly alone, yet often content, occasionally even happy," as when he catches glimpses of heaven in his exploration of the beautiful and the good."--Jacket
1. Autobiography: My Angle -- 2. World Stage and Public Events -- 3. Personal: From Parents to Stone -- 4. Intimate: From Justice to Love -- 5. Salvation by Geography -- 6. A Good Life?
Includes bibliographical references (pages 135-138)
Keywords: Tuan, Yi-fu, -- 1930-2022; Geographers -- Biography; Chinese Americans -- Biography